Taxonomy, systematics, and typification of Carex markgrafii Kük. (Cyperaceae) - Mesterházy, Attila; Jiménez-Mejías, Pedro; Pifkó, Dániel; Barina, Zoltán (Phytotaxa, 2018)
Carex markgrafii is a species described from Albania and known only from a single locality (Shen Ndue) in the central part of the country. The type specimen was destroyed during the World War II, and to date there was very little additional information about this taxon. During the fieldwork on the type locality, a small population of this species was found. We performed a morphological and DNA-based phylogenetic study to figure out the relationships of this species. Carex markgrafii was found to be nested among the European members of section Mitratae. The collected specimens were morphologically distinct from all the other species of the section on the continent. We designate the original illustration in protologue as the lectotype for C. markgrafii, and our new collection as epytype. A detailed description of the species and an identification key is provided.